Increasing the Ability to Solve Story Problems through the Implementation of the NHT Type Cooperative Model in Class V SD Negeri Sindet - hasanah, estri nur; Aprisca, Alya Pinky; Aini, Latifah Nuur; Mas'ud, Azza Ilvana (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2024)
This research is aimed at improving the ability to solve stories through the application of cooperative model of the NHT type in students of grade V SD State Sindet. The research is Class Action Research (PTK) with the research model Kemmis and Taggart. The subjects of this study were in the state of Sindet's fifth grade from April until August 2024. This class action research is carried out in two cycles, with each cycle consisting of planning, action, observation, and reflection. The data collection techniques used are observations, surveys, documentation, and written tests. The results of the research show that the application of cooperative models like NHT can improve the ability to solve stories. This can be seen in the first cycle 37.5% of students obtain a score above KKM and in the second cycle 93.75% of students get a score over KKM. Students' learning activity from an average of 72.5 in the 2nd cycle has increased to 75.9. Implementation of class actions has reached the criteria of success in this Study, which is 93,75% students can complete a story with a rating above KKK. This increase is due to the application of the cooperative model of the NHT type.